PODOLOGICAL ASPECTS OF FOOT CARE IN SOCIAL CARE CENTERS - Harju, Sintija; Akermane, Ruta; Saulīte, Mārīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Investigate the necessity for therapeutic foot care and the involvement of a podologist in an interdisciplinary health care team in social care institutions in Latvia.So far, no study has been conducted on the need for therapeutic pediatric care for Social Care Center (SCC) clients in Latvia; it is known that in individual SCC’s where some podologists work part-time, another podologist is invited in specific cases, or clients are taken to a podologist at a medical institution.The study was conducted in 15 Latvian Social Care Centers (SCC), surveying 750 customer feet. People who, for various reasons, are no longer capable of foot care, is a highly necessary specialist who will do it professionally and according the needs of each client, so the involvement of a podologist in the SCC team's work is essential. The foot healing provided by the podologist would help prevent diabetes, cardiovascular, musculoskeletal etc. complications caused by the disease; those clients whose age (range of motion, vision problems, etc.) no longer allows them to care for their feet.Methods: Qualitative and Quantitative Research Method. Research tool – foot examination protocol.